PERAN PENGAWAS KEPATUHAN DI BANK SYARIAH MANDIRI - Santoso, Deddy Rahmat; Triyowono, Iwan; Ludigdo, Unti (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2014)
This research try to capture a case that showing the â€Pengawas Kepatuhanâ€ (PKP) character in commercial debt on Bank Syariah Mandiri (BSM) and also showing the conventional characteristics. This research is a kind of qualitative research that using case study method. This is also trying to capture the compliance division duties and all kind of action in commercial debt in BSM. The summery try to showing some of PKPâ€™s characteristics when they guide in compliance function. Some of characteristics define in some phaseas: dealing phase,Â analyze phase, and debt withdrawal phase. The summery have captured some characteristics as general character on regulation, ex-ante agent character,Â auditor character and reporter character. In this characteristics, the conventional actions showing on some facts about the apathy attitude, the entertain action and also fraud action which direct some attitude on disobey actions in BSM. Disobey actions become a challenge in real characteristic of PKP which is the preventive ideology should be strive between the regulation idealism and also the sharia principal.